Potential Land for Durian Plant (Durio Zibethinus Murr) In Mungkajang Sub-District Palopo City - Karim, Hariyanti; Zhiddiq, Sulaiman; Suprapta, Suprapta (Universitas Negeri Makassar, 2017)
Durian is a fruit native to southeast asia plants were asked to become king of tropical fruit and has been recognized as the native species of the archipelago. Durian crop development in the region have great hope in order to improve the economy of rural communities. This research aims to know land suitability for Durian plant in Subdistrict of Mungkajang Palopo City. In taking sample use purposive sampling method. The point in talking sample is determined by a map of land units. The analysis technical data by using matching method.Â Results from this research that, of the 9 land units in the study area has two land suitability clasess, namely the research refers that suitable of marginal (S3) spread in 5 units land width it is 2619,6 Ha the units land are D2,III, Kbc,La; D1,II, Htn,Li; D2,II, Kbc,La; D2,I, Kbc,La; and D2,I, Swh,Al and for suitability class is not suitable (N) spread in 4 units land width it is 1130 Ha the units land are D1,IV, Htn,Li; D2,IV, Htn,La; D1,V, Htn,Li; and D2,V, Htn,La. Conclusions land suitability classes durian cultivation in the subdistrict of Mungkajang that is suitable of marginal (S3) spread in 5 units land and not suitable (N) spread in 4 units land. Heaviest limiting factor is temperature, rainfall, slope, and the effective depth of the soil.